PERLINDUNGAN DATA PRIBADI BAGI PENGGUNA SOSIAL MEDIA - saripa rugaya, Muh.Rifqy Hidayatullah Arham; Jafar, Usman; Jamil (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2025)
This research aims to analyze forms of personal data protection on social media and the implementation of personal data protection on social media. The problem raised was related to the increasing number of cases of personal data leakage on social media. The research method used is this research is a type of field research and the author uses a legal approach and a syar'i normative approach. The data sources used in this research are primary data and secondary data. The data collection methods used by researchers to conduct this research are observation, interviews and documentation. The results of this research are forms of personal data protection on social media in the form of personal data processors, personal data controllers, and personal data subjects who are not only people but also companies/legal entities. Implementing personal data protection, the Ministry of Communications and Information Technology (Kominfo) has a system called the Indonesia Data Protection System (IDPS). IDPS is a system that is able to minimize cyber crime, especially the misuse of personal data and information. The implementation of this system works directly with the social media application manager in this case (META).